Baianas de Acarajé against FIFA: Coloniality Nowadays (Alternautas, 2022)
This article presents the case of the conflict between the baianas de acarajé and the Fédération Internationale de Football Association (International Federation of Football Associations – FIFA), in Salvador, Brazil, analyzed in my master dissertation developed between 2013 and 2015. Due the FIFA World Cup in Brazil in 2014, baianas de acarajé, a productive group of black women whose craft is considered immaterial patrimony of afro-Brazilian culture, faced the possibility of being prohibited to work during the games of the championship. Starting in 2012, baianas de acarajé started a struggle against FIFA and the Brazilian state through demonstrations on the streets, collection of signatures via virtual petition and negotiation with the state. After this struggle, some baianas of the Association of Baianas de Acarajé (ABAM) were able to work in the Arena Fonte Nova of Salvador, in the city of Salvador (Brazil), in accordance with FIFA requirements. However, as evidenced by the ethnographic work, most of them had their right to work violated, and had to find other means of obtaining income in the period. It presents some results of the investigation about this struggle, undertaken in Salvador de Bahia between 2013 and 2014, based on the following questions: How did the relationship between baianas de acarajé and FIFA form and develop? How did the baianas de acarajé reacted and what did this dispute mean for the performance of their craft? In this scenario, it was possible to identify an amefrican pattern of resistance and survival of baianas de acarajé, with the circumstantial mobilization of the category of heritage as well as other strategies of struggle. From this case, the characteristics of the current pattern of exploitation and domination of capitalism and how the coloniality of power, of being and of knowledge are manifested can be analyzed.